INFLUENCE USE VIDEOS ANIMATION TO LEARNING OUTCOMES STUDENTS OF SMPN 2 PANCARIJAN - A. Yudistira Yusbani; Usman M; Nurmayanti (Indonesian Journal of Education (INJOE), 2023)
The purpose of this study is to understand how using video animation affects learning outcomes for students in SMPN 2 Pancarijang. The purpose of this study is to determine the impact of using video animation on the learning outcomes for IPA students in grade VIII at SMP Negeri 2 Pancarijang. The study uses a quantitative methodology with a true experimental design with a posttest-only control group design. 77 eighth-grade students from SMPN 2 Pancarijang made up the majority of the study's sample, which employed Cluster Random Sampling and included around 26 eighth-grade students. There are two variables in this essay: the use of video animation (variable bebas) and the results Students.data collection technique utilising documentation and tests. Data from the tests that were completed were then analysed using the t-test and the rumus mean. Based on the results of the data analysis, it is estimated that there are 78,4615 for the experimental group and 68,8462 for the control group. The independent sample t- test yielded Sig-2 tailed 0,784 > Sig-2 tailed 0,05.According to the results of the study, it can be concluded that the hypothesis (H1) that states that the use of video animation has a negative impact on the results of the study on students of Junior high School 2 Pancarijang "accepted" is true.